Pengaruh Pembelajaran Online terhadap Employability skill Mahasiswa Fakultas Teknik Universitas Negeri GorontaloPengaruh Pembelajaran Online terhadap Employability Skill Mahasiswa Fakultas Teknik Universitas Negeri Gorontalo - Eduart Wolok; Hasanuddin Hasanuddin; Sunardi Sunardi; Monica Pratiwi (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
This study aims to determine the effect of online learning on the employability skills of students of the Faculty of Engineering, State University of Gorontalo. The method used in this study is a quantitative correlational method. Correlation research is research that aims to determine whether there is a relationship between two or more variables. In this study, data processing was carried out using SPSS version 25.0. The sample of this research was 177 students from class of 2017, Faculty of Engineering, State University of Gorontalo. Research data collection techniques using a questionnaire. Analysis prerequisite tests include normality tests, linearity tests, and multicollinearity tests. Hypothesis testing includes simple regression analysis. The results of the study show: There is a significant effect of online learning on the employability skills of students of the Faculty of Engineering, State University of Gorontalo by 2.8%.